2015
DOI: 10.1097/md.0000000000001041
|View full text |Cite
|
Sign up to set email alerts
|

Subcapsular Hepatic Hematoma After Endoscopic Retrograde Cholangiopancreatography

Abstract: Endoscopic retrograde cholangiopancreatography (ERCP) is one of the most frequently performed procedures for the diagnosis and treatment of biliary-pancreatic diseases. ERCP-related complications total around 2.5% to 8%, with a mortality rate ranging from 0.5% to 1%. An exceptional ERCP complication is subcapsular hepatic hematoma, and few cases are reported worldwide.We present the case of a 52-year-old woman with a history of recurring upper abdominal pain and a clinical and ultrasonographic diagnosis of obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 18 publications
1
19
0
12
Order By: Relevance
“…Subcapsular hepatic hematomaafter ERCP is extremely uncommon and was firstly described in 2000 [5]. Since then more than 20 cases were reported in the literature [3], and just one of them is from Turkey [6]. Here we report an unusual case of post-ERCP hepatic subcapsular hematoma.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Subcapsular hepatic hematomaafter ERCP is extremely uncommon and was firstly described in 2000 [5]. Since then more than 20 cases were reported in the literature [3], and just one of them is from Turkey [6]. Here we report an unusual case of post-ERCP hepatic subcapsular hematoma.…”
Section: Introductionmentioning
confidence: 79%
“…Most common complications related to ERCP are pancreatitis, cholangitis, perforation and bleeding due to the papillotomy [2]. Complications related to this procedure vary from 2.5% to 8%, with a mortality rate of 0.5% to 1% [3][4]. Subcapsular hepatic hematomaafter ERCP is extremely uncommon and was firstly described in 2000 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have explained that subcapsular hepatic hematoma was related to infections from accidental puncture with non-sterile guide-wire and resulting in rupture of small intrahepatic vessels during endoscopy procedure in all cases worldwide [3]. Interestingly, the systematic review and metaanalysis reported that the prophylactic effectiveness of the nonsteroidal anti-inflammatory drugs can reduce the pancreatitis following ERCP [12].…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic Retrograde Cholangiopancreatography (ERCP), which was introduced into the field of gastroenterology, hepatology and hepato-pancreatico-biliary surgery, has progressed to be an important and essential diagnostic and therapeutic tool for biliary and pancreatic diseases but haemorrhagic complications usually occurs when utilizing Endoscopic Sphincterotomy (EST) or Endoscopic Papillotomy (EPT) [1][2][3][4]. The complication of subcapsular hepatic hematoma after conducting ERCP is uncommon and a likely life-threatening situation in which few cases was reported in the world [5].…”
Section: Introductionmentioning
confidence: 99%
“…The ERCP-related complications around 2.5-9%, with a mortality rate ranging from 0.6-1% [1]. Post-ERCP pancreatitis, perforation, cholangitis and post-sphincterotomy bleeding are the most frequently described complications [2,3].…”
Section: Introductionmentioning
confidence: 99%